Sound Radiation by a Cylindrical Open Cavity with a Surface Source at the Bottom - SZEMELA, Krzysztof (Archives of Acoustics, 2018)
The rigorous solution describing the sound radiation by an arbitrary surface source located at the bottom of a cylindrical open cavity embedded in a flat baffle has been obtained. The open cavities of different shapes can be found in some architectural structures as well as are components of sensors, musical instruments and vehicles. The presented formulas have been expressed in the form of infinite sums. To use them, the infinite sums have to be truncated to the finite number of terms. Therefore, in practice, the results obtain based on the proposed solution are not exact and their accuracy is determined by the truncation error. The use of presented formulas is an alternative method for the finite element method (FEM). However, taking into account that the calculation efficiency of FEM rapidly decrease when a volume of considered region increases, the obtained in this study solution can be more useful in some practical cases. The approximated formula of a high computational efficiency has been presented for the sound pressure in the far field. The sound radiation has been analyzed for a rectangular piston as a sound source. The influence of cavity depth ratio on the radiation efficiency has been investigated. The cases for which the cavity radiation efficiency can be approximately calculated from the formula valid for a baffled sound source have been determined.